ELECTRONIC POWER CONVERTER OF A 5-PHASE ASYNCHRONOUS MOTOR (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2024)
This presentation refers to the realization and testing of an experimental model of AC drive system based on a 5-phase asynchronous motor, made in the power range of 3-6 kW, and on a dedicated electronic converter, developed to ensure the power of a light electric vehicle, powered by electric batteries.